Polymerase Synthesis of DNA Containing Iodinated Pyrimidine or 7-Deazapurine Nucleobases and Their Post-synthetic Modifications through the Suzuki-Miyaura Cross-Coupling Reactions - Sýkorová, Veronika; Tichý, Michal; Hocek, Michal (Chembiochem, 2022)
All four iodinated 2'-deoxyribonucleoside triphosphates (dNTPs) derived from 5-iodouracil, 5-iodocytosine, 7-iodo-7-deazaadenine and 7-iodo-7-deazaguanine were prepared and studied as substrates for KOD XL DNA polymerase. All of the nucleotides were readily incorporated by primer extension and by PCR amplification to form DNA containing iodinated nucleobases. Systematic study of the Suzuki-Miyaura cross-coupling reactions with two bulkier arylboronic acids revealed that the 5-iodopyrimidines were more reactive and gave cross-coupling products both in the terminal or internal position in single-stranded oligonucleotides (ssONs) and in the terminal position of double-stranded DNA (dsDNA), whereas the 7-iodo-7-deazapurines were less reactive and gave cross-coupling products only in the terminal position. None of the four iodinated bases reacted in an internal position of dsDNA. These findings are useful for the use of the iodinated nucleobases for post-synthetic modification of DNA with functional groups for various applications.
Keywords: nucleotides; puriny; DNA-dependentní DNA-polymerasy; Nucleosides; pyrimidiny; Halogenation; oligonucleotides; Molecular Conformation; bioconjugations; nukleosidy; Pyrimidines; cross-coupling reactions; DNA-Directed DNA Polymerase; molekulární konformace; DNA; halogenace; Purines